Clinical diagnostic features and surgical outcomes of mesial temporal lobe epilepsy - O. P. Subbotina; L. M. Tibekina; S. N. Tonyan (Вестник хирургии имени И.И. Грекова)
Despite certain successes in the treatment of epilepsy, primarily associated with the active development of pharmacology, in 30% of cases, there is a resistant course, especially focal forms of temporal lobe epilepsy. Mesial temporal sclerosis (MTS) is one of the most common causes of drug-resistant epilepsy. Conservative treatment could help only in 90–92 % of cases. In other cases, surgical treatment is required for improving the quality of life of such patients. However, the percentage of surgical care for epilepsy remains low. Structured information on clinical signs, diagnostic techniques, approaches to surgical treatment and its outcomes should contribute to understanding the problem among specialists. Data on the effectiveness of operations in patients with drug-resistant epilepsy can help in timely hightechnology care for patients with mesial temporal lobe epilepsy.